THE GREAT RESET AND THE NEAR-TERM IMPLICATIONS FOR THE CHINESE ECONOMY: A POST PANDEMIC OUTLOOK - Reghunadhan, Ramnath; Karackattu, Joe Thomas (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The Great Reset has had a severe impact on the Chinese economy, with implications domestically, and on the global supply chain. One consequence has been the decline in the overall market demand in China, with a significant negative impact on infrastructure development and the labour industry. A unique aspect is a survey is to analyze the impact of COVID-19 on innovation and integration of digital technologies in China. The authors explicate the impact of the Great Reset on the Chinese economy, the implications on the supply chains that China is a crucial part of, and the global implications thereof.